The δ expansion and the principle of minimal sensitivity - Krein, G. [UNESP]; Menezes, D. P.; Nielsen, M.; Pinto, M. B. (FapUNIFESP (SciELO), 1998)
The δ-expansion is a nonperturbative approach for field theoretic models which combines the techniques of perturbation theory and the variational principle. Different ways of implementing the principle of minimal sensitivity to the δ-expansion produce in general different results for observables. For illustration we use the Nambu-Jona-Lasinio model for chiral symmetry restoration at finite density and compare results with those obtained with the Hartree-Fock approximation.